Edukasi Keuangan Syariah bagi Siswa SD Negeri 102028 Desa Sei Parit: Menabung Sejak Dini - Muhammad Akhdan Bahy; Pani Akhiruddin Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The 2025 Independent Community Service Program (KKN) of the University of Muhammadiyah North Sumatra was held at SD Negeri 102028 Sei Parit, Sei Rampah District, Serdang Bedagai Regency. Sharia financial education from an early age is an important step in shaping a generation that is financially literate and has Islamic morals. This study aims to describe the process and results of Islamic financial education activities through the “Saving from an Early Age” program for students at State Elementary School 102028 Sei Parit, Sei Rampah District, Serdang Berdagai Regency. The implementation method used a participatory approach with direct observation, counseling, mini banking simulations, and educational games. The results of the activity show that students are able to understand the basic concepts of saving, recognize the prohibition of usury, and show a high interest in saving consistently. This activity also succeeded in fostering basic Islamic financial literacy, especially in the context of wise pocket money management. This study recommends that similar programs be carried out continuously through collaboration between schools and Islamic financial institutions.